Analisis Struktural pada Puisi ‘Kangen’ karya W.S Rendra - Susilo, Salsabila Yasmin; Warsiman, Warsiman (Universitas Lampung, 2025)
This study analyzes the relationship between physical structure and inner structure in the poem Kangen by W.S. Rendra which is included in the book Empat Kumpulan Sajak in the Malam Stanza section, so that the study can contribute to literary studies by providing additional insight into the poet's interpretation in conveying the contents of the poem 'Kangen' which tells about his love for his wife, especially in the Malam Stanza section. By using a qualitative descriptive method, this study uses reading and note-taking techniques to analyze data in written form. Structural theory is applied to describe the elements of poetry, especially the physical and inner structures. This allows for a better understanding of the meaning of the poem without referring to external factors. The includes the use of connotative diction, figures of speech such as metaphors, hyperbole, and repetition, concrete words, similes, and low-pitched rhymes or rhythms. In addition, typographic aspects such as the use of capital letters and complete punctuation are also analyzed. The inner structure includes emotions, tones, themes, and moral messages conveyed in the poem. These two structures do not stand alone but complement each other so as to provide depth of meaning. The relationship between physical and spiritual structures arouses the reader's emotions, allowing them to understand and appreciate the contents of the poem more deeply. In conclusion, the meaning of the poem 'Kangen' as a whole is formed by the integration of physical and spiritual structures. The results of this study are expected to deepen the understanding between the structure of poetry and the meaning contained therein, as well as add a new descriptive perspective that has not been found in previous studies so that it can inspire other writers and poets in composing poetry.Keywords: Malam Stanza, Structural Approach, Poetry, W.S Rendra